Letramento científico, letramento em língua materna e a abordagem ciência, tecnologia, sociedade e ambiente: indicadores e possibilidades para o ensino de ciências - RIBEIRO, Dayane Negrão Carvalho (Universidade Federal do Pará, 2022)
This research was motivated by the professional and personal experiences of the teacher and author of this thesis and aimed to understand the development processes of scientific literacy and literacy in the mother tongue, based on teaching practices through the Science, Technology, Society and Environment (STSE) approach, and also to identify indicators of these processes. For the development of the research it was necessary to define and defend the use of the concepts and theoretical basis of the STSE approach, literacy in the mother tongue and scientific literacy as well as its relationship with science research and teaching. The methodology of the study adopted a qualitative approach, from the pedagogical intervention type, which took place in a public elementary and high school, in a municipality in the state of Pará, with the participation of students graduating from the 6th year of elementary school. The activities developed during the intervention were based on the socio-environmental theme “The Tidal Phenomenon”, considering scientific, technological, social and environmental implications of this theme, from the perspective of Teaching by Research. The instruments used for the constitution of data were: audio and video recordings, photographs, questionnaires, registration of students' activities and the teacher's research diary. For data analysis and interpretation, Discursive Textual Analysis (DTA) was used. Through the results, the thesis defends that science teaching activities through the STSE approach in elementary school, from the perspective of the involved study, promote learning with the development of scientific literacy and literacy in the mother tongue, showing indicators. The constituted data allowed us to verify that the teaching activities through the STSE approach enable contributions regarding the expansion of the students' vision, the expression of everyday language and the development of scientific language, with natural conditions of reading and writing and the adoption of a more active attitude. The development of activities also led to the proposition of indicators of scientific literacy processes in the mother tongue, observed in the analysis, to evidence the construction of scientific knowledge and reading and writing skills through the STSE approach, considering the decision-making capacity development process. The indicators are: obtaining information, organizing information, interpreting information, articulating text and context, communicating ideas, preparing questions, articulating term and concept, analysis and judgment, expression of action strategies and selection of action. These indicators were organized into three grouping blocks. They are: Reading and Contextualization; Thought and Integration; Decision and Action. The results allow us to affirm that the students were in the process of developing scientific literacy in their mother tongue and that this research contributes to the field of Science Teaching, representing advances in the construction of knowledge from the perspective of teaching and training of teachers.